The general perception of Islamic Investment among the community of UiTM Puncak Alam / Mohamad Syafiq Shamsuddin - Shamsuddin, Mohamad Syafiq (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This research has discussed people‟s perception in Islamic investment among the community in UiTM Puncak Alam Campus. In Malaysia, the Islamic bank institutions need or have to compete with the conventional bank institutions as a confidention to the society. It also aims to convince people about the importance of Islamic investment by analysing its purpose and objective of the investment. The research methodology will be used in this research are interview method and library research. The researcher make an interview session to 15 informant consist of students and lecturer who teached and studied at UiTM Puncak Alam Campus.